2022
DOI: 10.3390/life12050677
|View full text |Cite
|
Sign up to set email alerts
|

Structural Responses of Nucleic Acids to Mars-Relevant Salts at Deep Subsurface Conditions

Abstract: High pressure deep subsurface environments of Mars may harbor high concentrations of dissolved salts, such as perchlorates, yet we know little about how these salts influence the conditions for life, particularly in combination with high hydrostatic pressure. We investigated the effects of high magnesium perchlorate concentrations compared to sodium and magnesium chloride salts and high pressure on the conformational dynamics and stability of double-stranded B-DNA and, as a representative of a non-canonical DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 36 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…The stability of the DNA duplex has long been investigated as a function of temperature [4,5], but there have been relatively few studies of the effects of hydrostatic pressure [7,28,29]. The helix-coil transition temperature Tm is the characteristic parameter that defines how the duplex resists unwinding and the denaturation (separation in single strands) induced by heat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The stability of the DNA duplex has long been investigated as a function of temperature [4,5], but there have been relatively few studies of the effects of hydrostatic pressure [7,28,29]. The helix-coil transition temperature Tm is the characteristic parameter that defines how the duplex resists unwinding and the denaturation (separation in single strands) induced by heat.…”
Section: Discussionmentioning
confidence: 99%
“…The helix-coil transition temperature Tm is the characteristic parameter that defines how the duplex resists unwinding and the denaturation (separation in single strands) induced by heat. As far as pressure is concerned, exhaustive studies were less documented until recently [28,29]. As the Watson-Crick base pairing is associated with a negative DV, it was just concluded that DNA would be stabilized by (or at least very resistant to) external pressure [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(B) Graphical schematic summary of the conformational changes of the human telomeric G-quadruplex (G4Q) as a function of temperature, pressure, and cosolutes. The osmolyte TMAO and the crowding agent Ficoll 70, a polysaccharide of 5 nm hydrodynamic radius, as well as salt (Na + ) shift the equilibrium toward the antiparallel conformation. , Medium high temperatures and pressures lead to an equilibrium shift toward the parallel/hybrid conformation of the G4Q, higher temperatures and pressures finally to the unfolding of the G-quadruplex structure.…”
mentioning
confidence: 99%